New integration of MCDM methods and QFD in the selection of green suppliers - Yazdani, Morteza; Hashemkhani Zolfani, Sarfaraz; Zavadskas, Edmundas Kazimieras (Journal of Business Economics and Management, 2016)
Currently, topics of operations management and supply chain systems have been gaining more interest of researchers. Efficiency in supply chain activities and operations management firstly benefit organisations. One of the main operations in supply chain systems is the collaboration with selected suppliers. Various models have been proposed in terms of supplier evaluation and selection studies. The invention of a new integrated frame for the building of an effective supplier evaluation system is a multi-attribute task that consists of several factors as external and internal variables. This paper delivers a creative integrated model of supplier selection problem using SWARA, QFD and a new MCDM tool called WASPAS. This work considers customer attitudes in the process of supplier evaluation. To give more weight to customer requirements, a new SWARA method has been designed; additionally, QFD and the house of quality matrix have been used to transform customer requirements into the supplier evaluation index. Finally, WASPAS has been used to rate the performance of suppliers and present supplier ranking scores. Application of initiative ways to propose a systematic supplier selection problem has always been encouraged by supply chain managers. This topic has been addressed in this paper as well. First published online: 19 May 2016